Tenencia y uso del suelo en el corredor biológico rural del caño Zuría - Villavicencio. ¿Problema ambiental o de seguridad alimentaria? (Revista "Boletín el Conuco", 2020)
The importance of the presented theme allows to relate the territorial studies and the participation of the social actors next to the normativity focused on the environmental management. The topic of work takes as a point of study the rural sector of the municipality of Villavicencio and the subjects of the biological corridors.A biological corridor integrates socially with the inhabitants of a municipality in a territory, it maintains a series of relations associated to different types of events like zones of encounter, preservation of the identity, conservation of the environment, creation of water, among others, and these relations are to show the approximation between rural space and urban reality, in what Laubstein emphasizes as a continum approach (2011).
Keywords: land; tenure; land use; resilience; UAF; POT; JEL P28; R11; R14